The Cost of Populism: Evidence from history - Manuel Funke; Moritz Schularick; Christoph Trebesch (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
The rise of populism in the past two decades has motivated much work on its drivers, but less is known about its economic and political consequences. This column uses a comprehensive cross-country database on populism dating back to 1900 to offer a historical, long-run perspective. It shows that (1) populism has a long history and is serial in nature – if countries have been governed by a populist once, they are much more likely to see another populist coming to office in the future; (2) populist leadership is economically costly, with a notable long-run decline in consumption and output; and (3) populism is politically disruptive, fostering instability and institutional decay. The analysis suggests that populism is here to stay.
Keywords: 330